Perovskite thin film gas passivation method and laminated solar cell

Through the passivation process of heat injection gas, the problem of the problem that traditional passivation process is difficult to passivate the new defects caused by the perovskite film in high temperature metastable state is solved, and a more efficient passivation effect is achieved, thereby improving the stacked solar cells performance and stability.

CN119403414APending Publication Date: 2025-02-07SHENZHEN HIKING PV TECHNOLOGY CO LTD

Patent Information

Application Number
CN202510000545.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Traditional passivation processes are difficult to effectively passivate new defects caused by perovskite films in high temperature metastable states, resulting in limited photoelectric conversion efficiency and stability of crystalline silicon/perovskite stacked solar cells.

Method used

By placing the perovskite film in a closed container, passing it into a passivation gas (such as oxygen or chlorine) and heating it to form a passivation layer, which can passivate existing defects inside the film. It can passivate the possible new defect sites.

Benefits of technology

It significantly improves the passivation effect, inhibits the phase separation phenomenon of wide-bandgap perovskites, and improves the photoelectric conversion efficiency and stability of crystalline silicon/perovskite stacked solar cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119403414A_ABST
    Figure CN119403414A_ABST
Patent Text Reader

Abstract

The invention provides a perovskite thin film gas passivation method and a laminated solar cell, and belongs to the technical field of perovskite crystal silicon laminated solar energy, a hot injection gas passivation process is adopted to improve the passivation effect, a prepared perovskite thin film is placed in a closed container, and the perovskite thin film is subjected to gas passivation and heating to obtain the perovskite thin film. According to the invention, defects existing in the perovskite thin film can be passivated, sites where defects are possibly generated in the perovskite at high temperature can be passivated, internal defects of the thin film are reduced, the phase separation phenomenon of broadband gap perovskite is effectively inhibited, and the photoelectric conversion efficiency and stability of the crystalline silicon / perovskite laminated solar cell are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of perovskite tandem solar cells, and in particular to a perovskite thin film gas passivation method and a tandem solar cell. Background Art

[0002] Solar energy is a new type of clean energy that has attracted much attention, with the advantages of abundant resources and low cost. At present, photovoltaic cells are one of the most effective ways to convert solar energy into electrical energy, and solar cells such as single-crystal silicon and polycrystalline silicon have relatively mature industrialization technologies. In recent years, perovskite / crystalline silicon stacking technology has become one of the research hotspots in the field of photovoltaic technology and has attracted widespread attention. The development of this technology is of great significance to improving the photoelectric conversion efficiency of solar cells and reducing manufacturing costs, thereby promoting the further development and application of solar power generation technology. The theoretical effective photoelectric conversion efficiency of crystalline silicon / perovskite stacking solar cells is as high as more than 40%, which is much higher than that of crystalline silicon solar cells. The basic principle of perovskite / crystalline silicon stacking technology is to stack perovskite materials and crystalline silicon materials together to form a heterojunction, and to improve the photoelectric conversion efficiency of solar cells by utilizing the wide band gap, high absorption coefficient and high carrier mobility of perovskite materials and the stability and good electron transmission performance of crystalline silicon materials.

[0003] At present, the photoelectric conversion efficiency of crystalline silicon / perovskite tandem solar cells has exceeded 34%. Although there is still a gap with the theoretical value, there is still a lot of room for improvement. In addition, the stability problem is also a challenge that needs to be solved. Among them, the optimization of the perovskite absorption layer is one of the key points of tandem solar cells. The absorption layer is prone to surface or interface defects, causing a large number of non-radiative recombination, which leads to a decrease in the photoelectric and stability performance of the battery device. In the specific wide-bandgap perovskite light-absorbing layer required for tandem cells, its unique photoinduced phase separation phenomenon will also cause more defects in the film, thereby affecting efficiency and stability.

[0004] In the traditional method, a passivation layer is prepared on the perovskite absorption layer to reduce defects inside the crystal and improve the efficiency and stability of the device. Although there are many effective passivation methods, most of them are ineffective for some potential sites in the film where defects may occur. In addition, in crystalline silicon / perovskite tandem solar cells, the required perovskite film is a wide-bandgap perovskite with a bandgap of 1.68-1.73eV, which has the characteristics of phase separation and is more likely to produce new defects under operating conditions. Common passivation methods are to process steady-state perovskite films stored at room temperature. These methods can effectively passivate defects that already exist in wide-bandgap perovskite films under steady-state conditions.

[0005] However, under normal working conditions of photovoltaic devices, the device temperature can be as high as 50-80 degrees Celsius. Under such working conditions, the perovskite film is in a high-temperature metastable state, especially the wide-bandgap perovskite, which is prone to phase separation of iodine and bromine, resulting in new defects. Common passivation methods lack the passivation effect on the new defects generated by such metastable perovskite films under high temperature conditions, making it difficult to further improve the photoelectric conversion efficiency and stability of crystalline silicon / perovskite tandem solar cells. Summary of the invention

[0006] In order to solve the problem of poor effect of traditional passivation process on device operation under high temperature conditions, the present invention provides a perovskite thin film gas passivation method and a stacked solar cell, which adopts a hot injection gas passivation process to improve the passivation effect, and the prepared perovskite film is placed in a closed container. Through the passivation gas and heating, not only the existing defects in the perovskite film can be passivated, but also the sites where defects may be generated in the perovskite under high temperature conditions can be passivated, thereby reducing the internal defects of the film, effectively inhibiting the phase separation phenomenon of wide-bandgap perovskite, and improving the photoelectric conversion efficiency and stability of the crystalline silicon / perovskite stacked solar cell.

[0007] To achieve the above object, the specific scheme provided by the present invention is as follows:

[0008] A gas passivation method for a perovskite film comprises the following steps:

[0009] A battery substrate is provided, a perovskite layer is prepared on the surface of the battery substrate, the battery substrate is placed in a sealed container, a passivation gas is introduced and heated, and a passivation layer is formed on the surface of the perovskite layer.

[0010] Furthermore, the passivation gas is one of O2 (oxygen) and Cl2 (chlorine).

[0011] Furthermore, the heating temperature is controlled to be 40-120 degrees Celsius, the heating time is between 1-60 minutes, and the gas flow rate is 50 sccm.

[0012] Preferably, the heating temperature is controlled to be 80 degrees Celsius and the heating time is 30 minutes.

[0013] The present invention also provides a stacked solar cell, which comprises, from bottom to top, a crystalline silicon bottom cell, a tunneling layer and a perovskite top cell, wherein the perovskite top cell comprises a hole transport layer, a perovskite layer, a passivation layer, an electron transport layer, a second transparent electrode layer, a second metal electrode layer and an anti-reflection layer arranged on the tunneling layer, and the passivation layer is prepared by the above-mentioned perovskite preparation method.

[0014] Furthermore, the perovskite layer is an ABX3 structure, wherein the A position is an organic cation, including CH3NH3+ (MA + ), NH2CH=NH2 + (FA + )、CH3CH2NH3 + or Cs + At least one of;

[0015] The B position is a metal cation, including Pb 2+ Sn 2+ At least one of;

[0016] The X position is a halogen anion, including F - , Cl - Br - ,I - At least one of .

[0017] Furthermore, the crystalline silicon bottom cell can be selected from a crystalline silicon cell such as a pear cell, a topcon cell or a HJT cell;

[0018] Specifically, the crystalline silicon bottom cell includes, from bottom to top, a first metal electrode layer, a first transparent electrode layer, a P-type base doping layer, a base passivation layer, a textured crystalline silicon substrate, a base surface passivation layer and an N-type base doping layer.

[0019] In this embodiment, the surface of the textured crystalline silicon substrate is provided with a textured structure, which can reduce surface reflection and light escape, improve light capture efficiency, and thus improve photoelectric conversion efficiency.

[0020] The textured crystalline silicon substrate can be selected from one of intrinsic single crystal silicon, intrinsic polycrystalline silicon, N-type or P-type single crystal silicon.

[0021] In this embodiment, the hole transport layer is poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA), poly-3-hexylthiophene (P3HT), nickel oxide (NiO x ), molybdenum trioxide (MoO3), cuprous iodide (CuI), and cuprous thiocyanate (CuSCN).

[0022] In this embodiment, the electron transport layer is zinc oxide (ZnO), tin dioxide (SnO2), titanium dioxide (TiO2), [6,6] phenyl C 61 Methyl butyrate (PC 61 BM), carbon 60 (C 60 ), 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (BCP).

[0023] The buffer layer is composed of at least one of zinc oxide (ZnO), tin dioxide (SnO2) and titanium dioxide (TiO2).

[0024] In this embodiment, the first transparent electrode layer and the second transparent electrode layer are composed of at least one of indium tin oxide (ITO), indium zinc oxide (IZO), and aluminum zinc oxide (AZO).

[0025] In this embodiment, the first metal electrode layer and the second metal electrode layer are composed of at least one of silver (Ag), gold (Au), copper (Cu), aluminum (Al), and carbon (C).

[0026] In this embodiment, the anti-reflection layer is composed of at least one of magnesium fluoride, lithium fluoride (LiF), sodium fluoride (NaF), and silicon oxide (SiO2).

[0027] The present invention also provides a method for preparing the stacked solar cell, comprising the following steps:

[0028] A textured crystalline silicon substrate is provided, wherein a base passivation layer is prepared on the back of the textured crystalline silicon substrate, a P-type base doping layer is prepared on the surface of the base passivation layer, a first transparent electrode layer is prepared on the surface of the P-type base doping layer, and a first metal electrode layer is prepared on the surface of the first transparent electrode layer; and a base surface passivation layer is prepared on the surface of the textured crystalline silicon substrate, an N-type base doping layer is prepared on the surface of the base surface passivation layer, a tunneling layer is prepared on the surface of the N-type base doping layer, a hole transport layer is prepared on the surface of the tunneling layer, a perovskite layer is prepared on the surface of the hole transport layer, a passivation layer is prepared on the surface of the perovskite layer, an electron transport layer is prepared on the surface of the passivation layer, a buffer layer is prepared on the surface of the electron transport layer, a second transparent electrode layer is prepared on the surface of the buffer layer, a second metal electrode layer is prepared on the surface of the second transparent electrode layer, and an anti-reflection layer is prepared on the surface of the second metal electrode layer.

[0029] In order to saturate the dangling bonds on the surface of the textured crystalline silicon substrate, reduce the surface activity, increase the surface cleaning process, avoid the formation of recombination centers due to the introduction of impurities in the surface layer, and thereby reduce the surface recombination rate of minority carriers, a base passivation layer and a base surface passivation layer can be formed on the two surfaces of the textured crystalline silicon substrate respectively by vapor deposition, atomic layer deposition and the like.

[0030] In one embodiment, a phosphorus source / nitrogen source is diffused on a textured crystalline silicon substrate to form a doping structure, thereby obtaining the P-type base doping layer and the N-type base doping layer.

[0031] In one embodiment, the first transparent electrode layer is prepared by a magnetron sputtering method, wherein the prepared substrate sample is placed in a magnetron sputtering device for preparation, and the magnetron sputtering power is 50-200W;

[0032] In one embodiment, the first metal electrode layer is deposited by evaporation, including placing the prepared substrate sample on a mask plate for evaporation, and the evaporation vacuum is 5×10 -5 -2×10 -4 Pa, the evaporation temperature is 500-2000℃, and the evaporation rate is 0.1-5Å / S;

[0033] In one embodiment, the tunneling layer is used to solve the problem of electrical mismatch and device instability between two series-connected batteries, and can be prepared by atomic layer deposition, magnetron sputtering or wet chemical method.

[0034] In one embodiment, the hole transport layer is formed by spin coating, which includes uniformly coating the hole transport layer dispersion on the surface of the tunnel layer, with a spin coating speed of 1000-5000 rpm and a spin coating time of 10-100 s; after the spin coating, an annealing operation is performed, with an annealing temperature of 300-600° C. and an annealing time of 10-50 min.

[0035] Optionally, the hole transport layer may also be formed by magnetron sputtering, specifically, placing the prepared substrate sample in a magnetron sputtering device with a control power of 30-90W.

[0036] In one embodiment, the perovskite layer can be prepared by a flash evaporation method, including the steps of: dissolving perovskite powder in DMF and DMSO solvents, stirring to obtain a perovskite precursor solution, placing the battery substrate on a spin coater, setting the spin coating speed to 3500rpm, the spin coating time to 30s, and applying 120ul of the perovskite precursor solution on the surface of the battery substrate. After the spin coating is completed, transfer it to a flash evaporation table, set the flash evaporation time to 30s, and the flash evaporation temperature to 30°C. After the flash evaporation is completed, annealing is performed, the annealing temperature is set to 100°C, and the annealing time is 15 min to obtain a perovskite layer with a thickness of about 500nm.

[0037] Furthermore, the perovskite powder has an ABX3 structure, wherein the A position is an organic cation, including CH3NH3 + (MA + ), NH2CH=NH2 + (FA + )、CH3CH2NH3 + or Cs + At least one of;

[0038] The B position is a metal cation, including Pb 2+ Sn 2+ At least one of;

[0039] The X position is a halogen anion, including F - , Cl - Br - ,I - At least one of .

[0040] In one embodiment, the electron transport layer is formed by spin coating, specifically, the electron transport layer dispersion is uniformly spin coated on the surface of the passivation layer, the spin coating speed is 500-4000 rpm, and the spin coating time is 10-80 s;

[0041] Optionally, the electron transport layer can also be deposited by evaporation to evaporate the electron transport layer material onto the surface of the passivation layer, and the evaporation vacuum degree is 5×10 -5 -5×10 -4 Pa, the evaporation temperature is 100-400℃, and the evaporation rate is 0.05-1Å / S;

[0042] In one embodiment, the buffer layer is deposited by atomic layer deposition, which includes depositing the buffer layer material onto the surface of the electron transport layer using an atomic layer deposition device, and the deposition vacuum is 0-1×10 4 Pa, the deposition pipeline temperature is between 50-150°C, and the deposition chamber temperature is 40-150°C;

[0043] Optionally, the buffer layer can also be formed by evaporation to evaporate the buffer layer material onto the surface of the electron transport layer, and the evaporation vacuum is 6×10 -5 -4×10 -4 Pa, the evaporation temperature is 100-500℃, and the evaporation rate is 0.05-1Å / S;

[0044] In one embodiment, the second transparent electrode layer is formed by a magnetron sputtering method, including sputtering a transparent electrode material onto the surface of the buffer layer, with a control power of 30-200W;

[0045] Alternatively, the second transparent electrode layer may also be formed by evaporation of the transparent electrode material onto the surface of the buffer layer, with the evaporation vacuum being 1×10 -5 -5×10 -4 Pa, the evaporation temperature is 1000-2000℃, and the evaporation rate is 0.05-3Å / S.

[0046] In one embodiment, the anti-reflection layer can be prepared by magnetron sputtering or evaporation.

[0047] The present application provides a gas passivation method for a perovskite film and a stacked solar cell, which solves the problem that the conventional perovskite film passivation method cannot passivate the new defects generated by the perovskite film in the high-temperature metastable state, and improves the overall performance and stability of the device. The embodiment of the present application heats the prepared perovskite film to a metastable state by high-temperature heating, and then introduces a passivation gas. By using the infiltration of the passivation gas, not only can the existing defects inside the film be passivated, but also the sites where defects may be generated in the perovskite in the high-temperature metastable state can be passivated, further improving the passivation effect, suppressing the phase separation phenomenon of wide-bandgap perovskites, and improving the photoelectric conversion efficiency and stability of crystalline silicon / perovskite stacked solar cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 This is a step diagram of the gas passivation method for perovskite thin film described in the present invention;

[0049] Figure 2 is a schematic structural diagram of the stacked solar cell described in the present invention;

[0050] Figure 3 Schematic diagram of the operation of the traditional passivation method in a high temperature environment.

[0051] The reference numerals in the figure are: 10, battery substrate; 212, perovskite layer; 213, passivation layer;

[0052] 110, first metal electrode layer; 111, first transparent electrode layer; 112, P-type substrate doping layer; 113, substrate passivation layer; 114, suede crystalline silicon substrate; 115, substrate surface passivation layer; 116, N-type substrate doping layer; 117, tunneling layer;

[0053] 211, hole transport layer; 214, electron transport layer; 215, buffer layer; 216, second transparent electrode layer; 217, second metal electrode layer; 218, anti-reflection layer. DETAILED DESCRIPTION

[0054] The technical solutions in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0055] In the description of the present invention, unless otherwise specified, "multiple" means two or more; the terms "center", "longitudinal", "lateral", "up", "down", "left", "right", "inside", "outside", "front end", "rear end", "head", "tail", "vertical", "horizontal", "top", "bottom", "inside", "outside" and the like indicate the orientation or position relationship based on the orientation or position relationship shown in the drawings, which is only for the convenience of describing the present invention and simplifying the description, and does not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operate in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first", "second", "third" and the like are used for descriptive purposes only and cannot be understood as indicating or implying relative importance.

[0056] Under normal working conditions, the device temperature of photovoltaic devices can reach 50-80℃. In such high temperature environment, the perovskite film is in a high temperature metastable state, especially the wide bandgap perovskite, which is more likely to produce iodine and bromine phase separation and generate new defects. Figure 3 The traditional perovskite film passivation process is generally prepared at room temperature, and the passivation layer is prepared directly on the surface of the perovskite film. However, this passivation method has no way to further passivate the perovskite film, that is, it is difficult to passivate the defects generated by the device during normal operation.

[0057] See also Figure 1 The embodiment of the present application provides a gas passivation method for a perovskite film, providing a battery substrate 10, preparing a perovskite layer 212 on the surface of the battery substrate 10, placing it in a sealed container, introducing a passivation gas and heating it, and forming a passivation layer 213 on the surface of the perovskite layer 212. Different from the traditional perovskite film passivation process, the present application adopts a heating method to make the pre-prepared perovskite film in a metastable state. Passivation in this state can solve the potential defects formed during the operation of the device and improve the passivation effect; on the other hand, the passivation gas injection method is adopted in a high temperature environment, and the passivation gas can penetrate into the film, thereby improving the overall passivation effect of the film and suppressing the phase separation phenomenon, thereby improving the photoelectric conversion efficiency and stability of the stacked solar cell.

[0058] Furthermore, the passivation gas is one of O2 (oxygen) and Cl2 (chlorine).

[0059] Furthermore, the heating temperature is controlled to be 40-120 degrees Celsius, the heating time is between 1-60 minutes, and the gas flow rate is 50 sccm.

[0060] The following specific embodiments and comparative examples are provided to clearly and completely describe the technical solution of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0061] Example 1

[0062] See also Figure 1~Figure 2 This embodiment provides a stacked solar cell, including a crystalline silicon bottom cell, a tunneling layer 117, and a perovskite top cell. The crystalline silicon bottom cell includes, from bottom to top, a first metal electrode layer 110, a first transparent electrode layer 111, a P-type base doping layer 112, a base passivation layer 113, a velvet crystalline silicon substrate 114, a base surface passivation layer 115, and an N-type base doping layer 116. The perovskite top cell includes, from bottom to top, a hole transport layer 211, a perovskite layer 212, a passivation layer 213, an electron transport layer 214, a buffer layer 215, a second transparent electrode layer 216, a second metal electrode layer 217, and an anti-reflection layer 218. The passivation layer 213 is prepared by the above method. The preparation method of the stacked solar cell includes the following steps:

[0063] S (1) providing a textured crystalline silicon substrate 114, preparing a base passivation layer 113 on the back side of the textured crystalline silicon substrate 114, and diffusing a phosphorus source into the base passivation layer 113 to form a P-type base doping layer 112; preparing a base surface passivation layer 115 on the surface of the textured crystalline silicon substrate 114, and diffusing a nitrogen source into the base surface passivation layer 115 to form an N-type base doping layer 116.

[0064] S(2), preparation of the first transparent electrode layer 111:

[0065] The first transparent electrode layer 111 is prepared on the surface of the P-type base doping layer 112 by magnetron sputtering. The thickness of the first transparent electrode layer 111 is 100 nm. The target material of the magnetron sputtering is indium tin oxide (ITO). The power of the magnetron sputtering is 60 W. The operation time of the magnetron sputtering is 1.5 h.

[0066] S (3), preparation of the first metal electrode layer 110:

[0067] The substrate sample prepared in the previous step is placed on a mask, and silver (Ag) is evaporated onto the surface of the first transparent electrode layer 111 by evaporation to prepare the first metal electrode layer 110. The thickness of the first metal electrode layer 110 is 200 nm, wherein the vacuum degree of the evaporation method is 2×10 -4 Pa, the temperature is 800℃, and the evaporation rate is 2.5Å / S.

[0068] S (4), preparation of tunneling layer 117:

[0069] A tunneling layer 117 is prepared on the surface of the N-type base doping layer 116 . The thickness of the tunneling layer 117 is 40 nm. The power of the magnetron sputtering is 60 W and the operation time is 1 hour.

[0070] S (5), preparation of hole transport layer 211:

[0071] The tunneling layer 117 was cleaned with an ultraviolet ozone cleaner (UV-Ozone) for 15 minutes, 0.05 mol NiOx powder was dissolved in 1 mL ultrapure water, and ultrasonically vibrated for 20 minutes to prepare a hole transport layer dispersion. The hole transport layer dispersion was ultrasonically vibrated for 20 minutes and then uniformly coated on the surface of the tunneling layer 117. The hole transport layer 211 was prepared by spin coating and annealing. The thickness of the hole transport layer 211 was 20 nm. The spin coating speed of the spin coating method was 2000 rpm, the spin coating time was 40 s, the amount of the spin-coated solution was 100 ul, the annealing temperature was 450°C, and the annealing time was 30 min.

[0072] S (6), preparation of perovskite layer 212:

[0073] The perovskite layer 212 is prepared by a flash evaporation method, including the steps of: dissolving a perovskite powder having an ABX3 structure in DMF and DMSO solvents, stirring to obtain a perovskite precursor solution, placing the battery substrate on a spin coater, setting the spin coating speed to 3500 rpm, the spin coating time to 30 s, and coating the surface of the battery substrate with a perovskite precursor solution volume of 120 ul. After the spin coating is completed, transferring it to a flash evaporation table, setting the flash evaporation time to 30 s, and the flash evaporation temperature to 30°C, performing annealing after the flash evaporation, setting the annealing temperature to 100°C, and the annealing time to 15 min to obtain a perovskite layer with a thickness of about 500 nm.

[0074] S (7), preparation of passivation layer 213:

[0075] The passivation layer 213 is prepared by a hot injection gas passivation process. The substrate sample obtained in the above steps is placed in a high-temperature sealed container, Cl2 is introduced, the temperature of the container and the passivation gas is controlled to be 50°C, the gas flow rate is 50sccm, and the control time is 30min, and the passivation layer 213 is formed on the surface of the perovskite layer 212.

[0076] S (8), Preparation of electron transport layer 214:

[0077] C 60The electron transport layer 214 is prepared by evaporation to the surface of the passivation layer 213. The thickness of the electron transport layer 214 is 20 nm. The vacuum degree of the evaporation is 1×10 -4 Pa, the evaporation temperature is 200℃, and the evaporation rate is 0.1Å / S.

[0078] S (9), preparation of buffer layer 215:

[0079] SnO2 is deposited on the surface of the electron transport layer 214 by atomic layer deposition using an atomic layer deposition device to prepare the buffer layer 215. The thickness of the buffer layer 215 is 15 nm. The vacuum degree of the deposition is 0.5×10 4 Pa, the deposition channel temperature was 70 °C, and the deposition chamber temperature was 60 °C.

[0080] S (10), preparation of the second transparent electrode layer 216:

[0081] The second transparent electrode layer 216 is prepared on the surface of the buffer layer 215 by magnetron sputtering. The thickness of the second transparent electrode layer 216 is 100 nm. The target material of the magnetron sputtering is indium tin oxide (ITO). The power of the magnetron sputtering is 50 W. The operation time of the magnetron sputtering is 1 hour.

[0082] S (11), preparation of the second metal electrode layer 217:

[0083] The substrate sample prepared in the previous step is placed on the mask, and silver (Ag) is evaporated on the surface of the second transparent electrode layer 216 by evaporation to prepare the second metal electrode layer 217. The thickness of the second metal electrode layer 217 is 100 nm, wherein the vacuum degree of the evaporation is 2×10 -4 Pa, the temperature is 800℃, and the evaporation rate is 0.1Å / S.

[0084] S (12), preparation of anti-reflection layer 218:

[0085] The substrate sample prepared in the previous step is placed on the mask, and magnesium fluoride is evaporated onto the surface of the second metal electrode layer 217 by evaporation, and annealed to prepare the anti-reflection layer 218. The thickness of the anti-reflection layer 218 is 100 nm, and the evaporation vacuum is 2×10 -4 Pa, the evaporation temperature is 80°C, the evaporation rate is 2Å / S, the annealing temperature is 100°C, and the annealing time is 8min to obtain a stacked solar cell.

[0086] Example 2

[0087] The preparation process of the stacked solar cell in this embodiment is the same as that in Embodiment 2, except that in step S(7) of this embodiment, the temperature of the container and the passivation gas is controlled to be 80°C.

[0088] Example 3

[0089] The preparation process of the stacked solar cell in this embodiment is the same as that in Embodiment 2, except that in step S(7) of this embodiment, the temperature of the container and the passivation gas is controlled to be 100°C.

[0090] Comparative Example 1

[0091] The preparation method of the stacked solar cell in this comparative example is basically the same as that in Example 2, except that the passivation layer in this comparative example is prepared by a traditional passivation process, and the specific steps are:

[0092] A passivation layer dispersion liquid is prepared, wherein the passivation layer dispersion liquid is a solution obtained by dissolving propylenediamine iodine in an organic solvent such as methanol, ethanol or isopropanol, and ultrasonic dissolution is performed. The passivation layer dispersion liquid is uniformly coated on the surface of the perovskite layer and spin-coated. The propylenediamine iodine concentration is 0.5 mg / ml, the ultrasonic time is 30 min, the spin-coating speed is 6000 rpm, and the spin-coating time is 60 s. After the spin-coating is completed, an annealing operation is performed, the annealing temperature is 100° C., and the annealing time is 10 min, thereby obtaining a passivation layer on the perovskite layer.

[0093] The laminated solar cells obtained in Examples 1-3 and Comparative Example 1 were tested under the following test conditions: a standard solar intensity calibration was performed using a solar simulator, and a solar cell with an area of ​​1.0 cm 2 The device of the embodiment was subjected to IV test for a long period of time, the test temperature was maintained at 60° C., the starting voltage was set to 1.95 V, the cut-off voltage was set to 0 V, the range was set to 100 mA, and the result was rounded to one decimal place. The test results are shown in Table 1 below.

[0094] Table 1 shows the performance of the stacked solar cells in Examples 1-3 and Comparative Example 1

[0095] Photoelectric conversion efficiency (%) Open circuit voltage (V) <![CDATA[Short-circuit current density (mA / cm 2 ).]]> Decay rate (% / year) Example 1 29.5 1.80 19.7 0.8 Example 2 30.8 1.83 19.6 0.3 Example 3 30.2 1.82 19.7 0.5 Comparative Example 1 29.1 1.82 19.5 2.1

[0096] As shown in Table 1, the performance of the laminated solar cells described in Examples 1-3 and Comparative Example 1 is shown. The data obtained from the test show that Examples 1-3 introduce a hot gas injection passivation process when preparing the passivation layer, and the prepared perovskite film is excited to a metastable state and then subjected to a gas passivation treatment, which can not only passivate the existing defects in the perovskite film, but also passivate the sites where defects may occur in the perovskite under high temperature conditions, further improving the passivation effect. The examples 1-3 that introduce this process have a lower defect density and non-composite loss, and the obtained perovskite crystalline silicon laminated solar cells have a higher open circuit voltage and photoelectric conversion efficiency than Comparative Example 1. At the same time, the gas passivation method described in this application can also effectively suppress the phase separation phenomenon of wide bandgap perovskites, and improve the photoelectric conversion efficiency and stability of crystalline silicon / perovskite laminated solar cells. Compared with Comparative Example 1, Examples 1-3 that introduce this process have a lower efficiency decay rate. In the gas passivation method for perovskite film described in the present application, when the passivation temperature is controlled at 80°C, the passivation effect is optimal, which is reflected in that under high-temperature operation at 60 degrees, Example 1 has higher device performance and attenuation rate than Examples 1 and 3. When the passivation temperature is too low, the metastable state of the perovskite film is not sufficiently excited, resulting in poor passivation effect of internal defects in the film; when the passivation temperature is too high, although the passivation effect of the perovskite can be promoted, the excessively high temperature will cause the molecular diffusion efficiency of the device to accelerate, affecting the interface transmission efficiency, thereby reducing the performance of the entire device.

[0097] The above embodiments are only preferred implementation modes of the present invention. It should be pointed out that for ordinary technicians in this technical field, various changes, modifications, substitutions and deformations can be made to these embodiments without departing from the principles of the present invention. These technical solutions that are equivalent to the claims of the present invention all fall within the protection scope of the present invention, and the protection scope of the present invention is limited by the attached claims and their equivalents.

Claims

1. A gas passivation method for a perovskite film, characterized in that: The following steps are involved: A battery substrate is provided, a perovskite layer is prepared on the surface of the battery substrate, the battery substrate is placed in a sealed container, a passivation gas is introduced and heated, and a passivation layer is formed on the surface of the perovskite layer.

2. The gas passivation method for perovskite thin film according to claim 1, characterized in that: The passivation gas is one of O2 and Cl2.

3. The gas passivation method for perovskite thin film according to claim 1, characterized in that: The heating temperature is controlled to be 40-120 degrees Celsius, the heating time is between 1-60 minutes, and the gas flow rate is 50 sccm.

4. A stacked solar cell, characterized in that: It comprises a crystalline silicon bottom cell, a tunneling layer and a perovskite top cell, wherein the perovskite top cell comprises a hole transport layer, a perovskite layer, an electron transport layer, a second transparent electrode layer, a second metal electrode layer and an anti-reflection layer, and the passivation layer is prepared by the perovskite thin film gas passivation method according to any one of claims 1 to 3.

5. A tandem solar cell according to claim 4, characterized in that: The perovskite layer has an ABX3 structure, wherein the A position is an organic cation, including CH3NH3 + (MA + ), NH2CH=NH2 + (FA + )、CH3CH2NH3 + or Cs + At least one of; The B position is a metal cation, including Pb 2+ Sn 2+ At least one of; The X position is a halogen anion, including F - , Cl - Br - ,I - At least one of .

6. The tandem solar cell according to claim 4, characterized in that: The crystalline silicon bottom cell is selected from a crystalline silicon cell of a pear cell, a topcon cell or a HJT cell.

7. The tandem solar cell according to claim 4, characterized in that: The crystalline silicon bottom cell comprises, from bottom to top, a first metal electrode layer, a first transparent electrode layer, a P-type base doping layer, a base passivation layer, a velvet crystalline silicon substrate, a base surface passivation layer and an N-type base doping layer.

8. The tandem solar cell according to claim 4, characterized in that: The hole transport layer is poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA), poly-3-hexylthiophene (P3HT), nickel oxide (NiO x ), molybdenum trioxide (MoO3), cuprous iodide (CuI), and cuprous thiocyanate (CuSCN).

9. The tandem solar cell according to claim 4, characterized in that: The electron transport layer is zinc oxide (ZnO), tin dioxide (SnO2), titanium dioxide (TiO2), [6,6] phenyl C 61 Methyl butyrate (PC 61 BM), carbon 60 (C 60 ), 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (BCP).

10. A method for preparing a tandem solar cell, used for preparing a tandem solar cell as claimed in any one of claims 4 to 9, characterized in that: The following steps are involved: Providing a textured crystalline silicon substrate, preparing a base passivation layer on the back of the textured crystalline silicon substrate, preparing a P-type base doping layer on the surface of the base passivation layer, preparing a first transparent electrode layer on the surface of the P-type base doping layer, and preparing a first metal electrode layer on the surface of the first transparent electrode layer; And a substrate surface passivation layer is prepared on the surface of the velvet crystalline silicon substrate, an N-type substrate doping layer is prepared on the surface of the substrate surface passivation layer, a tunneling layer is prepared on the surface of the N-type substrate doping layer, a hole transport layer is prepared on the surface of the tunneling layer, a perovskite layer is prepared on the surface of the hole transport layer, a passivation layer is prepared on the surface of the perovskite layer, an electron transport layer is prepared on the surface of the passivation layer, a buffer layer is prepared on the surface of the electron transport layer, a second transparent electrode layer is prepared on the surface of the buffer layer, a second metal electrode layer is prepared on the surface of the second transparent electrode layer, and an anti-reflection layer is prepared on the surface of the second metal electrode layer.

Citation Information

Patent Citations

  • Method for improving performance of radiation detector based on CsPbBr3

    CN113013292A

  • Quantum dot light-emitting device, display panel, display device and manufacturing method

    CN114975803A

  • Perovskite layer preparation method, laminated solar cell and preparation method

    CN118890941A

  • Passivation device

    CN220342754U

  • KR20220059415A

Cited By

  • Perovskite thin film gas passivation method and tandem solar cell

    WO2026144175A1